2013
DOI: 10.1186/cc12518
|View full text |Cite
|
Sign up to set email alerts
|

Automated peritoneal lavage: an extremely rapid and safe way to induce hypothermia in post-resuscitation patients

Abstract: IntroductionMild therapeutic hypothermia (MTH) is a worldwide used therapy to improve neurological outcome in patients successfully resuscitated after cardiac arrest (CA). Preclinical data suggest that timing and speed of induction are related to reduction of secondary brain damage and improved outcome.MethodsAiming at a rapid induction and stable maintenance phase, MTH induced via continuous peritoneal lavage (PL) using the Velomedix® Inc. automated PL system was evaluated and compared to historical controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…When applying external cooling methods, freezing-induced skin damage and shivering need continuous attention 16. Invasive cooling can be achieved by peritoneal17 or gastric lavage with cold sterile fluids or intravenous cooling via rapid infusion of iced isotonic fluid. The latter is safe, easy and inexpensive to induce cooling.…”
Section: Discussionmentioning
confidence: 99%
“…When applying external cooling methods, freezing-induced skin damage and shivering need continuous attention 16. Invasive cooling can be achieved by peritoneal17 or gastric lavage with cold sterile fluids or intravenous cooling via rapid infusion of iced isotonic fluid. The latter is safe, easy and inexpensive to induce cooling.…”
Section: Discussionmentioning
confidence: 99%
“…A small observational study reported that peritoneal hypothermia in patients with STEMI and cardiac arrest is feasible and results in rapid cooling. 14 We therefore performed a multicenter randomized trial to assess the feasibility, safety, and efficacy of peritoneal hypothermia to reduce infarct size in patients with acute STEMI.…”
mentioning
confidence: 99%
“…Two Class III studies compared different invasive vs superficial cooling methods. 29,30 An additional Class III study 31 investigated the effect of a standardized treatment protocol. Because single Class III studies cannot drive recommendations, details of these studies are discussed only in the complete guideline.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%